Marketing strategies of green investments: basic concepts and specific features - Pimonenko, Tetiana; Liuliov, Oleksii; Us, Yana (Herald of Economics, 2019)
Due to the rapid increase of environmental concerns among consumers and their interest in purchasing eco-friendly and environmentally safe goods and services, a considerable amount of research has been carried out on theoretical and practical aspects of green marketing. Thus, the study provides an analysis of the role of environmental factor in enhancing competitive advantages of the company. The authors conclude that the growth of company competitiveness results in the greater interest of prospective investors in improving company environmental performance. The aim of the article is to systematize competitive strategies of green marketing aimed at attracting green investments. The authors claim that green marketing is based not only on the analysis of investment activity and estimation of project profitability, but also on sound decision-making in the developing and implementing environmental investment projects, which contribute to the reduction of CO2 emission and environmental pollution, improvement of resource and energy efficiency, conservation of biological diversity, etc. Taking into account research results from current studies, the authors consider green investments as traditional investment activities within projects aimed at improving environmental performance of companies. Based on the analysis of relevant studies, the key competitive strategies of green marketing for attracting green investments are iidentified.The authors come to the conclusion that in the contemporary society there are gender stereotypes which have a strong impact on consumers’ behaviour, and as a result, women and men have different views on green initiatives. It is found that with a more efficient use of resources some companies are able to pay off green investments, while other companies see creating a new eco-brand as the best way of achieving competitive advantages. The results of the article make it possible to assume that companies should develop green strategies, bearing in mind gender stereotypes and striving for more gender-neutral green products. The results of the article make it possible to further study specific features of green marketing strategies, attract more green investments and transform them into the source of competitive advantages.